The practice of confession and absolution as an agent of change in a prophetic Pentecostal Church during COVID-19 - Frahm-Arp, Maria (HTS teologiese studies, 2021)
During the coronavirus disease 2019 (COVID-19) pandemic in South Africa, one Prophetic Pentecostal Church, Rabboni Centre Ministries, brought about a marked change in their practice and theology of confession and absolution. Before COVID-19, the Prophet would exorcise the evil spirits that caused sinful behaviour in people and in this way restore them as good Christians acceptable to the congregation. During the COVID-19 lockdown, people could not meet in church and therefore the Prophet changed the practice and theology of confession and absolution. People had to personally identify their own sins and write these down in an email that they sent to the church. Their confessions were then read out, and they were given absolution by the Prophet. During COVID-19, sins were understood as the wrong actions and thoughts of believers, who were personally responsible for their sins. Sins were no longer blamed on Satan. No exorcism followed confessions, rather people were absolved by the Prophet just as people are absolved by priests in mainline churches. In this article, I show that through the act of self-reflection and confession, people are able to take control of their lives and determine their future selves. It also enables people to re-connect to the faith community, the Prophet and God.Contribution: Unlike the thesis of Weber and Foucault, this does not lead to heightened individualism but rather to a self-reflective individual who is aware both of their individual agency and their self as a ‘dividual’ being who is connected to other people and spirits.